2013
DOI: 10.1073/pnas.1317042110
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome missegregation rate predicts whether aneuploidy will promote or suppress tumors

Abstract: Significance Aneuploidy, an abnormal chromosome content that commonly occurs because of errors in chromosome segregation, can promote or suppress tumor formation. What determines how aneuploidy influences tumorigenesis has remained unclear. Here we show that the rate of chromosome missegregation, rather than the level of accumulated aneuploidy, determines the effect on tumors. Increasing the rate of chromosome missegregation beyond a certain threshold suppresses tumors by causing cell death. Increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
214
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(228 citation statements)
references
References 51 publications
10
214
3
1
Order By: Relevance
“…A strong cooperation between hepatocytes and mesenchymal cells and between the different nonparenchymal cell types occurs during liver injury (Gressner & Bachem, 1994). Meanwhile, the aneuploidy cells which appear in the sub‐G0/G1 population in our cell sorting analysis inherently trigger cell death (Liu et al ., 2012; Silk et al ., 2013). The increasing number of aneuploidy hepatocytes suggests an enhanced death of hepatocytes and consequently liver dysfunction and termination of mouse lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…A strong cooperation between hepatocytes and mesenchymal cells and between the different nonparenchymal cell types occurs during liver injury (Gressner & Bachem, 1994). Meanwhile, the aneuploidy cells which appear in the sub‐G0/G1 population in our cell sorting analysis inherently trigger cell death (Liu et al ., 2012; Silk et al ., 2013). The increasing number of aneuploidy hepatocytes suggests an enhanced death of hepatocytes and consequently liver dysfunction and termination of mouse lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…[16,32,72,95,96] These inconsistent findings may be explained by different rates and types of CIN in the various models. Indeed, it has been suggested that high rates of CIN inhibit tumor progression, while lower CIN rates allow for tumor evolution [5,93,94] (also see Figure 2b and c). Importantly, CIN does not only seem to affect cancer growth, but also the ability of cancer to adapt and spread as transient CIN induction can lead to tumor recurrence.…”
Section: Cin Can Have Highly Differential Effects On Cellsmentioning
confidence: 96%
“…[5,17,18,23,70] These mis-segregation events will lead to karyotype heterogeneity and karyotype evolution in the cell population and might explain the low rate of aneuploidy and karyotype evolution in cell cultures in which no (additional) CIN is induced (see Figure 2a for an example of karyotype evolution with low CIN). However, whether this "low-grade background" CIN rate is representative for the in vivo situation still needs to be assessed.…”
Section: Cin Can Have Highly Differential Effects On Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such multipolar mitoses, which result from the presence of extra centrosomes, provoke asymmetric cell divisions in which chromosomes are close-to-randomly distributed among three or more daughter cells (12,17). Exceptionally, newly generated aneuploid cells are fitter than their tetraploid progenitors, thus progressively transforming into malignant cells (2)(3)(4)(5)18).…”
mentioning
confidence: 99%